2002
DOI: 10.1007/s00414-001-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Rare failures in the amelogenin sex test

Abstract: Determination of sex using the amelogenin sex test is well established in the forensic field especially for casework and DNA databasing purposes. The sex test is part of commercially available PCR kits. Among 29,432 phenotypic male individuals stored in the Austrian National DNA database, 6 individuals were found to lack the amelogenin Y-specific PCR product which was confirmed using alternative amelogenin primers. The amplification of eight Y-chromosomal STR markers resulted in full profiles in five out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 25 publications
(25 reference statements)
2
79
0
5
Order By: Relevance
“…Several previous studies, however, have reported failures in amplifying the Y homologue due to Y chromosome deletions. 7,8 Roffey et al 9 reported failure to amplify the Y homologue from a normal male and attributed this failure to a mutation in the annealing region of the amelogenin primer because alternate amelogenin primers produced a Y product. Although the frequency of failing to amplify the Y chromosome is low [0.02% (6 of 29,432) in Austrian males, 7 1.85% (5 of 270) in Indian males, 8 8% (2 of 24) in Sri Lankan males 10 ], the consequences of failing to amplify the Y chromosome could be dramatic in forensic/rape cases, in identifying human remains from mass disasters, and for gender identification in the setting of prenatal diagnosis of X-linked recessive diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies, however, have reported failures in amplifying the Y homologue due to Y chromosome deletions. 7,8 Roffey et al 9 reported failure to amplify the Y homologue from a normal male and attributed this failure to a mutation in the annealing region of the amelogenin primer because alternate amelogenin primers produced a Y product. Although the frequency of failing to amplify the Y chromosome is low [0.02% (6 of 29,432) in Austrian males, 7 1.85% (5 of 270) in Indian males, 8 8% (2 of 24) in Sri Lankan males 10 ], the consequences of failing to amplify the Y chromosome could be dramatic in forensic/rape cases, in identifying human remains from mass disasters, and for gender identification in the setting of prenatal diagnosis of X-linked recessive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that multiple Y chromosome markers be analyzed in cases where sex identification is critical. 7 Failure to amplify the X chromosome would not be expected to lead to such consequences. However, if used quantitatively to determine and D), a normal female (B and E), and the case study male (C and F) were subjected to PCR using the Amel-A forward (FAM-labeled) and Amel-A reverse 1 (A to C) and Amel-A reverse 2 (D to F) primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used approach is based on the Amelogenin locus, which yields different-sized PCR (polymerase chain reaction) amplicons for the X and Y chromosome versions of the Amelogenin gene [71]. However, this method can misidentify males as females in some cases due to a deletion in the AMEL Y region [72][73][74]. While the frequency of the deletion is relatively low, the crucial nature of forensic test results in circumstances such as rape and prenatal gender determination where there is risk for male-specific inherited disorders makes any source of error a legitimate cause for concern.…”
Section: Mobile Element-based Human Gender Identificationmentioning
confidence: 99%
“…While the frequency of the deletion is relatively low, the crucial nature of forensic test results in circumstances such as rape and prenatal gender determination where there is risk for male-specific inherited disorders makes any source of error a legitimate cause for concern. This has led several researchers to recommend that Amelogenin should not be relied upon as the sole determinant of gender [72][73][74][75].…”
Section: Mobile Element-based Human Gender Identificationmentioning
confidence: 99%